Raingan kan suksa rueng kollayut rangngan sampan kan lek jang phunam kan yuen khor riekrong suan lae kan tobto kan nad yudngan (Arom Pongpangan Foundation)
The study report on the employer tactics against workers : fire the workers' leader, handling the counter requirements, and the counter measures against the general strike.